(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article provides useful information about assessment, assessment in education. Assessment plays an important role in teaching, regardless of the purpose. We all know that assessment in the education system, the examination of knowledge - clearly shows the results achieved. In addition, assessment is one of the aspects that allows students to see how they are mastering and how they are absorbing science-related skills. I also found it appropriate to dwell on specific and appropriate types of assessment. When it comes to evaluation, many think the goal is to get the result. Assessment is also a tool for the teacher on how to continue the teaching process. For an assessment to be useful, it must adapt itself to the mandatory standards and academic expectations of the particular context in which it occurs. The types of assessment depend on what purpose it is aimed at.